Pre-clinical modelling of rectal cancer to develop novel radiotherapy-based treatment strategies - Michael A. Gillespie; Colin W. Steele; Tamsin R.M. Lannagan; Owen J. Sansom; Campbell S.D. Roxburgh (Frontiers Media S.A., 2021)
Pre-operative chemoradiotherapy reduces local recurrence rates in locally advanced rectal cancer. 10-20% of patients undergo complete response to chemoradiotherapy, however, many patients show no response. The mechanisms underlying this are poorly understood; identifying molecular and immunological factors underpinning heterogeneous responses to chemoradiotherapy, will promote development of treatment strategies to improve responses and overcome resistance mechanisms. This review describes the advances made in pre-clinical modelling of colorectal cancer, including genetically engineered mouse models, transplantation models, patient derived organoids and radiotherapy platforms to study responses to chemoradiotherapy. Relevant literature was identified through the PubMed and MEDLINE databases, using the following keywords: rectal cancer; mouse models; organoids; neo-adjuvant treatment; radiotherapy; chemotherapy. By delineating the advantages and disadvantages of available models, we discuss how modelling techniques can be utilized to address current research priorities in locally advanced rectal cancer. We provide unique insight into the potential application of pre-clinical models in the development of novel neo-adjuvant treatment strategies, which will hopefully guide future clinical trials.